Pelatihan Penyusunan Business Model Canvas dalam Meningkatkan Jiwa Kewirausahaan Siswa SMK Kartini Surabaya - Dwi Bhakti Iriantini; Husni indrawati2; Giyana Giyana; Randy Randy (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Vocational high school is an educational model that aims to prepare its graduates to work, be able to choose a career, compete and develop themselves, fill the needs of the business world and the industrial world (dudi), and be productive, adaptive and creative. Therefore, vocational high school graduates are not focused on working, but rather emphasize the desire to become entrepreneurs. The purpose of this community service activity is to increase entrepreneurial knowledge so that students are motivated to become entrepreneurs and provide skills training in compiling Business Model Canvas for students of SMK Kartini Surabaya. It is hoped that in the future students will become reliable and professional entrepreneurs. This activity was carried out by the FEB UWKS community service team and in collaboration with SMK Kartini Surabaya, from May 2024 to August 2024. The number of students trained in entrepreneurship was 40 students. The training began with entrepreneurship and Business Model Canvas materials, then the practice of compiling Business Model Canvas was carried out, and ended with a discussion. The implementation of this PKM activity needs to be carried out sustainably. The results of the community service activities are that students have a Business Model Canvas as a business pla